Faktor Risiko Kejadian Diare pada Anak Usia 6-24 bulan di Kota Jambi - Gustika Trisiyani; Muhammad Syukri; Rd. Halim; Fahrul Islam (Poltekkes Kemenkes Padang, 2021)
Diarrhea is a major cause of child morbidity and mortality in developing countries, including Indonesia. This study aimed to determine the risk factors for diarrhea in children aged 6-24 months. This study used a case-control design with 48 cases and 48 controls. Cases were children aged 6-24 months who had experienced diarrhea with the ICD code A.09 recorded in the register book from October 2019 to March 2020. The control samples were children aged 6-24 months who did not suffer from diarrhea with age (range ±3 months), gender, and domiciled in the same village as the case. Samples were taken using the total sampling method. Data collection used interview and direct observation techniques in July 2020. Data analysis was carried out univariate and bivariate using the chi-square test. The results of the study showed the relationship between exclusive breastfeeding (p= 0.000 OR=4.8 95% CI: 2.04-11.53), use of milk bottles (p=0.000 OR=6.3 95%CI 2.5-15.7), and CTPS habits (p = 0.000 OR = 4.8 95% CI 2.0-11.5) with the incidence of diarrhea in children. Family latrines (p=0.168 OR=4.3 95%CI 0.4-39.7), and drinking water sources (p=1,000 OR=1.0 95%CI 0.1-16.4) were not factors diarrhea risk. Health workers should educate the importance of the habit of washing hands with soap and washing bottles. Parents should give exclusive breastfeeding, clean regularly, and pay attention to how to store milk bottles before use.